Influence of amyloid beta on impulse spiking of isolated hippocampal neurons - Yavorsky, Volodymyr A.; Rozumna, Nataliia M.; Lukyanetz, Elena A. (Frontiers in Cellular Neuroscience, 2023)
One of the causes of Alzheimer's disease is the formation of β-amyloid plaques, which ultimately lead to the dysfunction of neurons with subsequent neurodegeneration. Despite extensive research into the effects of various amyloid conformations, including oligomers and fibrils, on neuronal function, both in isolation and in circuits, the precise impact of extracellular beta amyloid on neurons is still not fully understood. This topic is the focus of investigation in numerous labs, and there is a large community of researchers working to unravel the complexities of this area of study. In our experiments, we studied the effect of β-amyloid peptide (Aβ1-42) on the action potential (APs) generation in isolated CA1 hippocampal neurons in perforated patch clamp conditions in vitro. We found that Aβ1-42 affects APs generation in neurons differently, but with the common enhancement of APs firing response within a minute after application begins. In the first type of response, the APs firing threshold of inward current shifts towards smaller values by 20-65%. The APs firing threshold was not changed with the second type of response to the Aβ1-42 application. For these neurons, Aβ1-42 caused a moderate increase in spiking frequency up to 15% with approximately the equal elevation in APs frequencies regardless of input current levels. Obtained data prove the absence of direct short-term negative effect of the Aβ1-42 on APs generation in neurons. Even with increasing the APs generation frequency and lowering the neurons' activation threshold, neurons were functional. Obtained data can suggest that only the long-acting presence of the Aβ1-42 in the cell environment can indirectly cause neuronal destruction due to a prolonged increase of APs firing and predisposition to this process.